Anti-interleukin 1 agents for the treatment of recurrent pericarditis: a systematic review and meta-analysis. Issue 15 (18th March 2021) - Imazio, Massimo; Andreis, Alessandro; Piroli, Francesco; Lazaros, George; Gattorno, Marco; Lewinter, Martin; Klein, Allan L; Brucato, Antonio
Abstract : Aims: Corticosteroid-dependent and colchicine-resistant recurrent pericarditis (RP) is a challenging management problem, in which conventional anti-inflammatory therapy (nonsteroidal anti-inflammatory drugs, colchicine, corticosteroids) is unable to control the disease. Recent data suggest a potential role for anti-interleukin-1 (IL-1) agents for this condition. This study was designed to assess the safety and efficacy of anti-IL-1 agents in this setting. Methods: We performed a systematic review and meta-analysis of randomised controlled trials and observational studies assessing pericarditis recurrences and drug-related adverse events in patients receiving anti-IL-1 drugs for pericarditis. Results: The meta-analysis assessed 7 studies including 397 pooled patients with RP. The median age was 42 years, 60% were women and the aetiology was idiopathic in 87%. After a median follow-up of 14 months (IQR, 12–39), patients receiving anti-IL-1 agents (anakinra or rilonacept) had a significantly reduction in pericarditis recurrences (incidence rate ratio 0.06, 95% CI 0.03 to 0.14), compared with placebo and/or standard medical therapy. Anti-IL-1 agents were associated with increased risk of adverse events compared with placebo (risk ratio (RR) 5.38, 95% CI 2.08 to 13.92): injection-site reactions occurred in 15/41 (36.6%) vs none (RR 14.98, 95% CI 2.09 to 107.09), infections occurred in 13/51 (25.5%) vs 3/41 (7.3%; RR 3.65, 95% CI 1.23 to 10.85). Anti-IL-1 agents were not associated with increased risk of severe adverse events. Conclusions: In patients with RP, anti-IL-1 agents (anakinra and rilonacept) are efficacious for prevention of recurrences, without severe adverse events.